Xylooligosaccharides from Barley Malt Residue Produced by Microwave-Assisted Enzymatic Hydrolysis and Their Potential Uses as Prebiotics - Shah Zaib Fareed; Pipat Tangjaidee; Tabkrich Khumsap; Wannaporn Klangpetch; Suphat Phongthai; Apinun Kanpiengjai; Chartchai Khanongnuch; Kridsada Unban (Plants)
Barley malt residue (BMR) was subjected to microwave-assisted enzymatic hydrolysis to evaluate its potential as a raw material to produce xylooligosaccharides (XOS) suitable for use as a prebiotic. The influent factors on XOS production, microwave power, exposure time, and xylanase dosage were ascertained with response surface methodology based on Box–Behnken design (BBD). The fitted models of XOS and xylose yields were in good agreement with the experimental results. Using a microwave power of 1235.1 W, a 6 min exposure time, and a xylanase concentration of 89.12 U/g substrate gave the highest yield of XOS: 208.05 mg/g substrate at 4 h of enzyme incubation time. Based on the product composition, BMR-XOS purification by Saccharomyces cerevisiae treatment was superior to the process of activated carbon adsorption and ethanol precipitation treatment and was selected for further experiments. Thin-Layer Chromatography (TLC) and high-performance liquid chromatography (HPLC) clearly elucidated the oligosaccharide compositions, and the result of Fourier Transform Infrared Spectroscopy (FTIR) confirms the molecular structure and sugar components of achieved BMR-XOS. In vitro fermentation of BMR-XOS obtained from this study by the selected probiotics, Lactococcus lactis TISTR 1401, Levicaseibacillus brevis FS 2.1, Lactobacillus casei TISTR 1463, showed similar prebiotic activity compared with the commercial XOS, galactooligosaccharides (GOS), xylose, and glucose (control). In conclusion, the present study was successful in establishing the use of barley malt residue for the extraction of xylan and XOS, which could be further used as a prebiotic.